ANALISIS KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS MENGGUNAKAN REGRESI LINEAR BERGANDA DI PT. LEMBAH KARET - Tri Ernita; Ali Sutan Nasution; Boby Aditya (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
PT. Lembah Karet is one company industry processing rubber natural Becomes rubber crumb (crumb rubber) which produces crumb Rubber SIR 20 with orientation export 95%. Destination country export biggest that is America union. PT Lembah Karet sued for always using K3 in work, thing this is recommended company not to happening accident and death workers, disruption of operational processes company, reducing production output, and the creation of poor industrial relations. Occupational Health Variables with score significant 0.000 < 0.05 then could concluded that Ho is rejected and Ha is accepted, it means Occupational Health by Partial take effect positive and significant to Productivity. More Occupational Health make safety work Becomes guaranteed. It caused because of good Occupational Health could make employee capable guard stability results productivity at PT. Rubber Valley Effect of Occupational Health and Safety where do 13% work? results this obtained from distributed questionnaire to employees of PT. Lembah Karet